Author correction: Voltage-independent GluN2A-type NMDA receptor Ca2+ signaling promotes audiogenic seizures, attentional and cognitive deficits in mice - Bertocchi, Ilaria; Eltokhi, Ahmed; Rozov, Andrei; Nguyen Chi, Vivan; Jensen, Vidar; Bus, Thorsten; Pawlak, Verena; Serafino, Marta; Sonntag, Hannah; Yang, Boyi; Burnashev, Nail; Li, Shi-Bin; et al. (Communications biology, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s42003-021-01717-x
Im Titel ist "2+" in Ca2+ hochgestellt
Gesehen am 01.07.2021